Socially-determined factors of positive transformation of the professional and labor self-concept of persons with musculosketal disorders - E. V. Istomina (Вестник университета, 2024)
The article studies social factors that determine the features of transformation of professional-labor self-concept in students with musculoskeletal disabilities studying under inclusive conditions in organizations of secondary vocational and higher education. The study was carried out on a sample of 106 students with musculoskeletal disorders of ﬁnal years of educational organizations, in whom positive, negative, and neutral forms of transformation were recorded during the study. It has been revealed that in the group of students characterized by positive changes in professional and personal development during education and professional training, the transition of maladaptive forms of professional and labor self-concept into adaptive ones that allow them to achieve success in professional development, the majority of them are those who have an extensive network of social contacts, including friends with disabilities, classmates, and other people without any disabilities, teachers, and professors who give them the opportunity to develop their professional self-concept. In this group, most students have high rates of satisfaction of basic psychological needs for autonomy, social contacts, and competence, whereas in the group of students characterized by negative transformation of professional and labor self-concept, many identify themselves only with the social group of disabled people, feel alienated from the outside world with excessively high rates of satisfaction of basic psychological needs, which demonstrates their helplessness and deprivation of conditions of their professional and personal development.